Fat cadherin modulates organ size in Drosophila via the Salvador/Warts/Hippo signaling pathway. - Bennett, F.C.; Harvey, K.F. (Current Biology, 2006)
The atypical Fat cadherin has long been known to control cell proliferation and organ size in Drosophila, but the mechanism by which Fat controls these processes has remained elusive. A newly emerging signaling pathway that controls organ size during development is the Salvador/Warts/Hippo pathway.Here we demonstrate that Fat limits organ size by modulating activity of the Salvador/Warts/Hippo pathway. ft interacts genetically with positive and negative regulators of this pathway, and tissue lacking fat closely phenocopies tissue deficient for genes that normally promote Salvador/Warts/Hippo pathway activity. Cells lacking fat grow and proliferate more quickly than their wild-type counterparts and exhibit delayed cell-cycle exit as a result of elevated expression of Cyclin E. fat mutant cells display partial insensitivity to normal developmental apoptosis cues and express increased levels of the anti-apoptotic DIAP1 protein. Collectively, these defects lead to increased organ size and organism lethality in fat mutant animals. Fat modulates Salvador/Warts/Hippo pathway activity by promoting abundance and localization of Expanded protein at the apical membrane of epithelial tissues.Fat restricts organ size during Drosophila development via the Salvador/Warts/Hippo pathway. These studies aid our understanding of developmental organ size control and have implications for human hyperproliferative disorders, such as cancers.